Can Percutaneous Biportal Endoscopic Surgery Achieve Enough Canal Decompression for Degenerative Lumbar Stenosis? Prospective Case–Control Study - Heo, Dong Hwa; Quillo-Olvera, Javier; Park, Choon Keun (World neurosurgery, 2018)
Recently, full-endoscopic lumbar decompression has shown encouraging clinical outcomes. However, there are no reports as to whether sufficient lumbar decompression through full-endoscopic procedures can be achieved. The purpose of this study is to investigate the radiologic outcomes of percutaneous biportal endoscopic decompression compared with those of conventional microscopic decompressive surgery. A case–control prospective study was carried out. Patients were classified into 2 groups regarding the operation method (microscope group and endoscopic group). The cross-sectional area of the dura was measured both preoperatively and postoperatively at 5 axial cuts of T2-weighted magnetic resonance images in all subjects. In addition, clinical outcomes using visual analog scale for back and leg pain and Oswestry Disability Index were analyzed. Radiologic and clinical results were compared between groups. A total of 88 patients were enrolled in the study. Forty-two patients were assigned to the microscope group and 46 patients were assigned to the endoscopic group. Postoperatively, the dura was significantly expanded in each group (P < 0.05). Visual analog scale and Oswestry Disability Index scores improved after surgery in both groups (P < 0.05). In addition, there was no significant difference of dura expansion between the 2 groups (P > 0.05). Immediate postoperative pain score was significantly greater in the microscope group than in the endoscopic group (P < 0.05). Full-endoscopic lumbar decompression using percutaneous biportal endoscopic approach is a safe and effective treatment for lumbar spinal stenosis. Decompression can be achieved with the percutaneous endoscopic technique at a similar rate to that achieved by the microscopic approach. •Biportal endoscopic surgery can achieve decompression similar to microscopic surgery.•Percutaneous biportal endoscopic surgery may be an effective treatment for lumbar stenosis.•Percutaneous biportal endoscopic surgery offers the advantages of reduced immediate postoperative pain.